2019
DOI: 10.1101/585471
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evaluation of BMP-mediated patterning in a 3D mathematical model of the zebrafish blastula embryo

Abstract: Bone Morphogenetic Proteins (BMPs) play an important role in dorsal-ventral (DV) patterning of the early zebrafish embryo. BMP signaling is regulated by a network of extracellular and intracellular factors that impact the range and signaling of BMP ligands. Recent advances in understanding the mechanism of pattern formation support a source-sink mechanism, however it is not clear how the source-sink mechanism shapes patterns in 3D, nor how sensitive the pattern is to biophysical rates and boundary conditions a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…DAPI was used at the last step to stain the nucleus, and the cells were mounted with Fluoromount-G (SouthernBiotech, Cat NO 0100-01). smFISH using RNAscope method on whole-mount embryos We used the protocol shown in our published paper (Li et al 2020). Detailed probe information and dilutions are shown in Table 3.…”
Section: Smfish Using Rnascope Methods On Cryosectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…DAPI was used at the last step to stain the nucleus, and the cells were mounted with Fluoromount-G (SouthernBiotech, Cat NO 0100-01). smFISH using RNAscope method on whole-mount embryos We used the protocol shown in our published paper (Li et al 2020). Detailed probe information and dilutions are shown in Table 3.…”
Section: Smfish Using Rnascope Methods On Cryosectionsmentioning
confidence: 99%
“…Our data implied that this mutual inhibition might play an essential role in BMP morphogen maintenance. To determine the impact of different szl expression on a three-dimensional level, we modi ed our previously built three-dimensional growing domain model, which includes the growth of epiboly and 3D patterning (Li et al 2020); the mathematical equations for this model are shown in Table 4. We adopted 182 sets of parameters screened from our 10 million 1D simulations (Tuazon et al 2020) and applied different expression regions of szl as simulation input, with margin (Fig.…”
Section: Determining Critical Factors In Quantifying Distribution Across Whole Embryosmentioning
confidence: 99%